The Influence of Social Media and Brand Awareness on University Students’ Purchase intention in E-Commerce - Melisa Jumatun Ulya; Nurlia Fusfita (Green Inflation: International Journal of Management and Strategic Business Leadership, 2025)
The rapid advancement of digital technology has spurred the growth of online shopping through e-commerce platforms. Among the factors suspected to influence the increasing purchase intention, especially among university students, are social media engagement and brand awareness. Students, as part of the digital native generation, are primary targets for e-commerce marketing through social media. However, the degree to which these factors affect students’ purchasing interest remains underexplored. This study aims to examine the influence of social media and brand awareness on students’ purchase intention in e-commerce products. A quantitative approach was employed using Partial Least Squares (PLS) analysis to assess the relationships between variables. The findings reveal that social media exerts a positive and significant effect on purchase intention, with an original sample value of 0.114, a p-value of 0.003, and a t-statistic of 2.944. Brand awareness demonstrates an even stronger impact, with an original sample value of 0.879, a p-value of 0.000, and a t-statistic of 25.567. These results confirm both hypotheses, indicating that more intensive and engaging social media activities by e-commerce platforms, coupled with higher brand awareness among students, significantly enhance their purchase intention in offered products. This study highlights the strategic importance of social media marketing and brand-building efforts in stimulating consumer interest within the student demographic. This study not only contributes to the theoretical understanding of consumer behavior in the digital age but also offers practical insights for e-commerce marketers targeting university students. The implications suggest that personalized and interactive content on social media can further strengthen engagement and brand recall. Future research could explore moderating variables such as trust, product type, or cultural background to deepen the analysis of purchase intention drivers.